Esercito, istituzioni, territorio. Alloggiamenti militari e «case herme» nello Stato di Milano (secoli XVI e XVII) - Alessandro Buono (Premio Tesi di Dottorato, 2009)
What was the impact of the armies of the King of Spain on one of the territories of its composite monarchy during the centuries of the early modern age? What changes took place in the relations of power between the local institutions and the Madrid headquarters, between the Lombard corps and the city of Milan, between the representatives of the territorial corps and the power élites, as a consequence of the grievous burden represented by the military costs necessary for running the war? These are some of the questions that the author attempts to answer through study of the phenomenon of the military garrisons, an exceptional vantage point for observing the fine line that, in the ancient regime, divided the "military" and "civilian" worlds, which were not yet separated by the high walls and barbed wire of modern barracks.